Análisis del diseño y operación de un sistema híbrido de trigeneración/fotovoltaico con aplicación al sector comercial - López Vega, Aldo (Universidad Michoacana de San Nicolás de Hidalgo, 2017)
Shopping centers consume a large amount of electrical and thermal energy during their daily operation to provide quality services and achieve the comfort conditions that customers need. However, the conventional way of obtaining these types of energy has been put to discussion due to the inefficiencies in the processes of transformation, distribution and transportation that it entails, as well as the damages that are generated in the environment due to the emission of gases to the atmosphere. Given these conditions, cogeneration / trigeneration systems supported by renewable energy are ideal schemes to meet energy needs in a more efficient and cost-effective manner. For this reason, a hybrid trigeneration / photovoltaic system was installed in a shopping mall in the city of Morelia (Michoacán, Mexico) to partially cover the electricity, heating and colling demands of the mall throughout the year. The plant consists of a gas microturbine of 65 kW electrical power, three absorption chillers of 5 TR each and a photovoltaic system composed of 108 modules of 280 W each, capable of generating a maximum peak of 30 kW of electrical power. This project was supported and promoted by the CONACYT Innovation Stimulus Program to demonstrate the feasibility of this type of energy generation schemes under current conditions in the Mexican energy context. The present study consists on finding the design in which the fossil resources are used in the most efficient manner and the strategy of operation under which a reduction of the current electric billing is obtained. This will be achieved by developing energy models based on the first and second law, whose will be validated through experimental data taken on site during the operation of the system.

Los centros comerciales consumen una gran cantidad de energía eléctrica y térmica durante su operación diaria para ofrecer servicios de calidad y lograr satisfacer las condiciones de confort que los clientes necesitan. Sin embargo, la forma convencional de obtener estos tipos de energía ha sido puesta a discusión debido a las ineficiencias en los procesos de trasformación, distribución y transportación que conlleva, así como los daños que se generan en el medio ambiente debido a la emisión de gases de efecto invernadero hacia la atmosfera. Dadas estas condiciones, los sistemas de cogeneración/trigeneración apoyados con energías renovables son esquemas ideales para cubrir las necesidades de energía de una forma más eficiente y rentable. Por esta razón se instaló un sistema híbrido de trigeneración/fotovoltaico en un centro comercial en la ciudad de Morelia (Michoacán, México) para cubrir de manera parcial las demandas de electricidad, calor y frio presentes en el mismo a lo largo del año. La planta consiste principalmente en una microturbina de gas de 65 kW de potencia eléctrica, tres enfriadores de absorción de 5 TR cada uno y un sistema fotovoltaico compuesto de 108 módulos de 280 W cada uno, capaz de generar un pico máximo de 30 kW de potencia eléctrica. Este proyecto fue apoyado y promovido por el Programa de Estímulos a la Innovación CONACYT para demostrar la factibilidad de este tipo de esquemas de generación de energía bajo las condiciones actuales en el contexto energético Mexicano. El presente estudio consiste en encontrar el diseño en el que los recursos fósiles sean aprovechados de la manera más eficiente y la estrategia de operación bajo la cual se consiga una disminución de la facturación eléctrica actual.
Facultad de Ingeniería Mecánica. Maestría Ciencias en Ingeniería Mecánica
Keywords: info:eu-repo/classification/cti/7; FIM-M-2017-0743; Sistema fotovoltaico; Modelado termodinámico; Eficiencia energética; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5539